Flexible and fire safe sandwich structured composites with superior electromagnetic interference shielding properties. (September 2022) - Chen, Kexin; Feng, Yuezhan; Shi, Yongqian; Wang, Hengrui; Fu, Libi; Liu, Miao; Lv, Yuancai; Yang, Fuqiang; Yu, Bin; Liu, Minghua; Song, Pingan
Abstract: The integration of outstanding flame retardancy and electromagnetic interference shielding effectiveness (EMI SE) in polymers is highly desirable for practical applications. In this work, thermoplastic polyurethane (TPU) composites loaded with silicon wrapped ammonium polyphosphate (SiAPP) and short carbon fiber (SCF) were prepared through melt blending method. Then, a novel air-assisted thermocompression technology independently developed by our group was employed to fabricate multifunctional sandwich-structured TPU/SiAPP/SCF/Ti3 C2 Tx MXene composites. The peak of heat release rate and the peak of smoke release rate of TPU composites containing 20 wt% SiAPP and 20 wt% SCF were decreased by 72.5% and 49.7%, respectively, compared to those of pure TPU. The sandwich structure endowed the TPU samples with high EMI SE. For instance, the TPU/SiAF20/MXene SW-1.02 mm composite inserted with the Ti3 C2 Tx MXene layer exhibited the averaged EMI SE of 50.5 dB.